Anxiogenic-like effect of acute and chronic fluoxetine on rats tested on the elevated plus-maze - M.T.A. Silva; C.R.R. Alves; E.M.M. Santarem (Brazilian Journal of Medical and Biological Research, 1999)
The selective serotonin reuptake inhibitor fluoxetine (FLX) is widely prescribed for depression and anxiety-related disorders. On the other hand, enhanced serotonergic transmission is known to be classically related to anxiety. In this study, the effects of acute (5.0 mg/kg) and chronic (5.0 mg/kg, 22 days) FLX were investigated in both food-deprived and non-deprived rats tested in the elevated plus-maze. Significant main effects of the three factors (drug, food condition and administration regimen) were observed, but no interaction between them. The administration of either acute or chronic FLX resulted in an anxiogenic effect, as detected by a significant reduction in the percentage of time spent in the open arms and in the percentage of open arm entries. Food deprivation yielded an anxiolytic-like profile, probably related to changes in locomotor activity. The administration regimen resulted in an anxiolytic profile in chronically treated rats, as would be expected after 22 days of regular handling. The anxiogenic action of acute FLX is consistent with both its neurochemical and clinical profile. The discrepancy between the anxiogenic profile of chronic FLX and its therapeutic uses is discussed in terms of possible differences between the type of anxiety that is measured in the plus-maze and the types of human anxiety that are alleviated by fluoxetine.